2016
DOI: 10.1002/vms3.21
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin E supplementation fails to impact measures of oxidative stress or the anaemia of feline chronic kidney disease: a randomised, double‐blinded placebo control study

Abstract: This study was designed to test the hypothesis that supplementation with vitamin E, an antioxidant, in cats with chronic kidney disease (CKD), would reduce oxidative stress and its impact on RBC membrane fragility, resulting in these cats maintaining a greater packed cell volume (PCV) compared with CKD cats not receiving supplementation.Thirty‐six cats with CKD were randomly assigned to receive either daily vitamin E or a placebo for 3 months in a double‐blinded study design.History and physical examination, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…In a previous study in CKD cats, 30 IU of vitamin E daily per cat had no effect on measures of oxidative stress or anaemia [ 41 ]. The authors suggested that the vitamin E dose may have been too low to be effective, although the vitamin E was not measured in the study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study in CKD cats, 30 IU of vitamin E daily per cat had no effect on measures of oxidative stress or anaemia [ 41 ]. The authors suggested that the vitamin E dose may have been too low to be effective, although the vitamin E was not measured in the study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study in CKD cats, 30 IU of vitamin E daily per cat had no effect on measures of oxidative stress or anaemia [ 41 ]. The authors suggested that the vitamin E dose may have been too low to be effective, although the vitamin E was not measured in the study [ 41 ]. Since there was a statistically significant increase in plasma vitamin E concentration in our study, we can assume that the selected vitamin E dose was appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations